First Alarm and Time of Diagnosis in Autism Spectrum Disorders. Issue 1 (2nd January 2022) - Mitroulaki, Sotiria; Serdari, Aspasia; Tripsianis, Gregory; Gundelfinger, Ronnie; Arvaniti, Aikaterini; Vorvolakos, Theofanis; Samakouri, Maria
ABSTRACT: Early diagnosis of autism spectrum disorder (ASD) is of paramount importance as it opens the road to early intervention, which is associated with better prognosis. However, early diagnosis is often delayed until preschool or school age. The purpose of the current retrospective study was to explore the age of recognition of first alarming symptoms in boys and girls as well as the age at diagnosis of different subtypes of ASD in a small sample. A total of 128 parents' of children with ASDs were participated in the survey by completing a self-report questionnaire about early signs and symptoms that raised their concern. Parents of children with autism voiced concerns earlier and obtained diagnosis significantly earlier compared to parents of children with Asperger syndrome ( p value <0.000). No significant difference ( p value<0.05) has been detected between males and females in early manifestation of first signs and symptoms of ASD. The mean age at diagnosis was 3.8 years for autistic disorder, 6.2 years for children with Asperger syndrome and 6.4 years for other, e.g., PDD-NOS. The most commonly reported symptoms were speech and language problems ( p value = 0.001) for children who were later diagnosed with autism, while behavior problems ( p value = 0.046) as well as difficulties in education at school ( p value = 0.013) for children with Asperger syndrome. The gap between early identification and diagnosis pinpoints the urgent need for national systematic early screening, the development of reliable and sensitive diagnostic instruments for infants and toddlers and heightened awareness of early signs of ASD among parents, teachers, and healthcare professionals and providers as well.